Eksposisi Frasa “Sebab Jika Kita Sengaja Berbuat Dosa” Berdasarkan Ibrani 10:26 - Aliadi, Frans (Jurnal Kala Nea, 2023)
The reason for the phrase "For if we sin willfully" in Hebrews 10:26 is to remind its readers of the importance of maintaining a godly life and avoiding sin, and to emphasize that it is only through faith in Christ and a godly life that we can obtain forgiveness of sins and eternal salvation. The letter to the Hebrews was written to Christian Jews living in the first century. They had received teaching about Christ and the Christian faith, but still faced pressure and persecution from their Jewish neighbors. This letter was written to strengthen their faith and help them understand how important their faith in Christ was. In this letter, the author teaches about the virtues of Christ as the high priest and the perfect sacrifice for the sins of mankind. He also teaches about the importance of maintaining faith and godly living in response to the grace and salvation that God has given through Christ. Hebrews 10:26 discusses the importance of Christ's sacrifice as the perfect offering for the sins of man. This verse emphasizes that if a person who has received the teaching of the truth deliberately commits sin, then he loses the opportunity to obtain forgiveness of sins.